2021
DOI: 10.7759/cureus.13789
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Stump Cancer Treated With Radiotherapy Using Computed Tomography-Guided Brachytherapy

Abstract: Cervical stump cancer, which arises in the remaining uterine cervix of a woman with a history of supravaginal hysterectomy, accounts for 1.6-4.4% of all cervical cancers. The close proximity of the rectosigmoid colon to the primary tumor, which is due to the absence of the uterine corpus, should be considered carefully in the treatment planning of brachytherapy. Although three-dimensional image-guided brachytherapy (3D-IGBT) is used widely to treat cervical cancer in those with an intact uterine corpus, the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, only one case report of IGABT has been published to date. The technique used and the results are comparable to ours [ 4 ]. Six retrospective studies have evaluated brachytherapy in cervical stump cancer [ 7 - 12 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…To the best of our knowledge, only one case report of IGABT has been published to date. The technique used and the results are comparable to ours [ 4 ]. Six retrospective studies have evaluated brachytherapy in cervical stump cancer [ 7 - 12 ].…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have reported the efficacy and feasibility of brachytherapy with cesium or radium sources, but to the best of our knowledge, there are very scarce data with modern image-guided brachytherapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Okada et al . reported a case of cervical stump cancer (T3bN1M0) successfully treated by combining external beam radiotherapy and CT-based IGBT [ 13 ]. Using tandem and ovoid applicators in brachytherapy, an EQD 2 of 69.6 Gy was delivered to the patient for HR-CTV.…”
Section: Discussionmentioning
confidence: 99%
“…Personal preferences should be made by women once informed with the correct information by her service provider, including the occurrence of a future cancerous tumour or its presence during the first surgery, the difficulty and complexity of a second surgery if needed, the presence of health complications including present and future, especially that of late diagnosis, the type of tumour, the degree of its distinctiveness, the health condition of the woman, and the difficulty in classifying the disease stage to develop the appropriate ideal treatment plan, which would deprive her of the ideal plan for her condition. Perhaps, the existence of therapeutic alternatives gives this category of patient treatment opportunities, such as radiotherapy and chemotherapy, or both [ 29 , 30 ]. The high percentage of health problems of the cervix is a warning bell and a warning signal that ought to be respected and taken into account, and the priorities of the surgical decision to treat uterine problems must be reviewed and rehabilitated within the surgical skills, provided that the speed factor does not involve conducting the operation, so posting the health problems of the future makes it more difficult, and adherence to the surgical and therapeutic foundations, line facilitate its way of healing and open a path to a renewed confidence.…”
Section: Discussionmentioning
confidence: 99%